Influence of Long-Term Application of Organic Fertilization on the Effects of DCD in Brown Soil. (June 2020) - Fang, Zhaohui; Huo, Renjie; Luo, Peiyu; Han, Xiaori; Yang, Jinfeng
Abstract: Nitrification (DCD) inhibitor has been proved to be effective in retarding nitrification process of nitrogen in the soil. Application of nitrification inhibitors to the field is considered to be a major method in controlling nonpoint pollution induced by nitrogen fertilizer in agricultural production. Thus a simulating experiment was carried out to study the Influence of long-term application of organic fertilization on the effects of different concentrations of Dicyandiamide in brown soil, and the best application rate was screened to provide references for agricultural practice. Soil samples (0-20cm) were taken from two treatments in October 2017: (1) no fertilization (CK); (2) pig manure input (M). The samples were sieved while still fresh and incubated at a constant temperature (25°C) and soil moisture in different treatments remained 60 percent of field water capacity for 42 days with periodic subsamplings. The experiment included unfertilized control, soil appended with urea nitrogen of 0.4g/kg alone, soil appended with urea nitrogen of 0.4g/kg and 1%DCD, soil appended with urea nitrogen of 0.4g/kg and 2%DCD and soil appended with urea nitrogen of 0.4g/kg and 5%DCD (The Percents represents the percentage of DCD depended on the amount of applied pure N). During the experimental period, the contents of ammonium nitrogen (NH4 + -N), nitrite nitrogen (NO3 - -N), pH and nitrification potential were measured. Results of laboratory incubations indicated that DCD effectively inhibited the transformation from ammonium nitrogen to nitrate nitrogen in brown soil and the trends were N+5%DCD > N+2%DCD > N+1%DCD>N. It was found that nitrification was always greater in long-term application of organic fertilizer soil than in long-term unfertilized soil. Long-term application of organic fertilizer reduced the inhibitory effect of DCD.